HUMANISTIC PSYCHOLOGY STUDY OF MAIN CHARACTER'S INNER CONFLICT IN PAULO COELHO'S NOVEL - Wahyuniar Wahyuniar; Angla Florensy Sauhenda; Elni Wahyuni (Universitas Musamus Merauke, 2023)
This study aims to describe the inner conflict of the main character in the novel Mata Hari. This type of research is descriptive qualitative. The source of the data in this study is the novel Mata Hari by Paulo Coelho. The data in this study are in the form of quotations that contain inner conflicts experienced by the main character. The method in this study is descriptive with a literary psychology approach. The technique used is literature study technique, namely content analysis. The research focus is Abraham Maslow's humanistic psychology study; (1) physiological needs, (2) safety, (3) love and belonging, (4) self-esteem/appreciation, and (5) self-actualization. The form of inner conflict is internal and external inner conflict. The results of the research show that there is an inner conflict experienced by the main character Mata Hari. Internal inner conflict, namely the main character was raped by the school principal when she was sixteen years old before the main character got to know the world and dived deeper to know the dark world. External inner conflict, in which the main character suffers greatly from accusations from her father, stepmother, and even her husband.